The Effect Of Attachment Style And Religiousity Toward Dating Violence Among Adolescent - Farah Hanifa Purnomo; Bambang Suryadi (‎‎‎TAZKIYA Journal of Psychology, 2017)
On adolescence, there are some changes that occur. One of them is emotionally changes that causing the interest feeling with opposite sex emerge. In this era, dating on adolescent is not a new thing. However, the impacts of dating become more serious. One of them is dating violence amongst adolescent couples. The objective of this study is to examine the effect of attachment style, religiousity and gender toward dating violence among adolescent. Samples are 209 students which were taken with convenience technique. The three scales that used in this study are dating violence scale, religiousity scale, and attachment style scale. Their validities are examined by confirmatory factor analysis (CFA). Meanwhile, the method that used is multiple regression. Findings were consistent with previous research. The findings show that religiousity, attachment style and gender has significant effect toward dating violence among adolescent. All of the independent variabels have implication about 10,5%, and the others were affected by variables outside the research. After the proportion variance were analyzed, the results show that fearful avoidant, which is dimension of attachment style, and gender are the biggest predictors toward dating violence. For better result, we suggest to use bigger sample size. DOI: 10.15408/tazkiya.v22i2.8404